Pesquisa-formação com professoras dos anos iniciais do Ensino Fundamental: narrativas de experiências formativas e o desenvolvimento profissional - Ronco, Carla Helena Bettini (2019)
The present work aimed to develop a reflective process about the experiences of inservice teacher education, lived by school teachers along their professional trajectory. The specific objectives were: to evoke, through narratives, the significant professional marks of teachers; share their formative experiences and identify, signs of a formative process that contributes to their professional development. In the construction of the work, within a qualitative approach, we opted for research-formation with the use of narratives. The theoretical framework is based on the following concepts: initial and inservice teacher education, by Canário, Imbernón and Nóvoa; narrative inquiry by Clandinin, Connelly, and Delory-Momberger; research-formation, by Josso; and life histories by Delory-Momberger, Josso, Passeggi and Nóvoa. Data collection is based on Passeggi's reflective group proposal and was made through five meetings, in which written and oral narratives and mandalas were produced about the life histories of four teachers of the early years of elementary school, who work in a private school in São Paulo. Data analysis was performed using Souza's (2004, 2014) three-step reading proposal. In this process, three Thematic Analysis Units (TAU) were identified: Link, Teacher education and Practice. Regarding the links, it was observed that the relationship with the family, work team and students lead significant experiences in the teachers' path, contributing to the professional constitution of each one. Regarding the TAU Teacher Education, it was observed that the initial and inservice teacher education gain more or less importance as a formative experience, according as they are reflected in the teaching practice. The teachers acknowledge that the education experienced in the school environment reveals the school culture and is a constitutive part of their professional identities, but they miss the formation that, in the short term, helps them face the daily routine of the classroom. In the analysis of TAU Practice, it was observed the importance of the protagonism of the teacher in the teaching practice and the reflection on the practice that allows the increase of their professional knowledge to deal with new situations. As a result, it was found that, for the teachers participating in this research, the experiences lived in the school environment, which contribute to their professional development, are those that observe the following guiding principles: the collaborative work, the knowledge sharing, the dialog between peers, the thinking over the practice, the protagonism of the teacher, the respect and the professional ethics. Another finding was that the potency of continued formation also depends on the seek for autonomy in their formation